Three new species of copepods (Copepoda: Calanoida and Cyclopoida) from anchialine habitats in Indonesia - Boxshall, Geoff A.; Jaume, Damià (Zootaxa, 2012)
Three new species of copepod crustaceans are described from material collected from anchialine and brackish habitats inand around the village of Walengkabola on the coast of Muna Island, to the southeast of Sulawesi. A new species of cy-clopoid, Paracyclopina sacklerae n. sp., was described from material collected from the tidal inflow entering into the bot-tom of sinkholes a few metres inland from the shoreline. Detailed comparisons are made with Paracyclopina orientalis(Lindberg, 1941), n. comb., a closely related congener here transferred from its original genus Cyclopetta Sars, 1913. Theassignment of Paracyclopina Smirnov, 1935 to the family Cyclopettidae is followed here despite uncertainty over the va-lidity of some of the families created by the break up of the former Cyclopinidae. Two new species of Boholina Fosshagen& Iliffe, 1989 are described, based on material from the same sinkholes and from caves located up to 700m inland fromthe coast and exhibiting further reduced salinity down to 1.8 ppt. One species, B. parapurgata n. sp., is very closely relatedto B. purgata Fosshagen & Iliffe, 1989 from Bohol island in the Philippines, the other B. munaensis n. sp., is very closelyrelated to B. crassicephala Fosshagen & Iliffe, 1989 also from Bohol island, but a number of fine scale differences in the leg 5 of both sexes are recognised in each case. Keys to valid species of both genera are provided.